The identity of the fossil Psilocephala tarsalis (Statz, 1940) (Diptera: Asiloidea) - Hauser, Martin; Fisher, Eric M. (Zootaxa, 2007)
Fossils are crucial to our understanding of the evolution of organisms. They provide minimum dates for the occurrence of taxa, show past distribution patterns, and are important for establishing phylogenetic hypotheses. The value of a fossil depends to an important degree on the accuracy of its classification. Unfortunately, fossils are difficult to correctly classify, as they display only a small percentage of characters which are discernable in living organisms. Continuing advance in systematic knowledge, leading to increasingly complex classifications, create an ongoing need for a reevaluation of previously described fossils